Which type of employment uncertainty matters when becoming a parent? An analysis by educational attainment in the United Kingdom - Brian Buh (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2022)
Multiple studies find that employment uncertainty has a negative association with the timing of first birth. However, there is significant debate about how to conceptualise and measure employment uncertainty-as contemporaneous objective measures, subjective perceptions, or early-career employment instability. Sex and education appear to determine which measures associate with delays in first birth timing. This study aims to empirically examine the influence of various employment uncertainty measures on individual timing of first birth by including social stratification and considering the relieving influences of partnership. It uses event history analysis starting three years after the end of formal education to examine how employment uncertainty is associated with the timing of first birth, differentiated by education. It employs data from the United Kingdom Household Longitudinal Study 2009-2020. The results indicate that employment uncertainty has a particularly negative association with timing of first birth among low educated individuals. For medium and high educated individuals, much of the significance disappears when adding partnership, but largely remains for low educated individuals. Contemporaneous objective measures like being employed at the time of interview accelerates the timing of first birth for women, while part-time work delays it for men. Low educated women who report that they are likely to lose their job in the next twelve months have an increased likelihood of first birth. Early-career joblessness appears to only delay first birth for low educated individuals.
Keywords: 300; Employment Uncertainty; Fertility; Measuring Uncertainty; First Birth; Event History Analysis; Understanding Society